Estimating Import-Demand Function in ARDL Framework - Abdul Rashid; Tayyaba Razzaq (Economics and Econometrics Research Institute (EERI), 2010)
We develop a structural econometric model of import demand for Pakistan, with binding foreign exchange constraint. ARDL and DOLS techniques are used to estimate the log-run coefficients of price and income elasticities. The empirical results from ARDL bound testing approach and Johansen's method for cointegration show strong evidence of the existence of a long-run stable relationship among the variables included in the import demand model. The price and income elasticity estimates have correct signs and are statistically significant. The coefficient of scarcity premium, as it appeared statistically significant with correct sign, confirms the presence of a binding foreign exchange constraint on aggregate import demand, particularly before the period of trade liberalization.
Keywords: F14; O16; 330; Import Demand; Foreign Exchange Constraint; ARDL; DOLS; Pakistan